A Study of the Indonesian Translation of '花 (Huā)' in Polysemous Words from a Cognitive Perspective - Die, Chen; Syaifullah, Aceng Ruhendi (Humanus, 2025)
This study analyzes the polysemy phenomenon of the word "花 (Huā)" in Mandarin from a cognitive semantic perspective, as well as its translation strategies into Indonesian. This study employs a qualitative descriptive design. Data collection involved identifying and extracting all occurrences of “花” from the corpus. Analysis was guided by Rosch’s Prototype Theory (1978), Fillmore’s Frame Semantics (1982), and Lakoff & Johnson’s Conceptual Metaphor Theory (1980). The research finds that the word "Huā" carries various meanings, ranging from its basic sense to metaphorical and metonymic interpretations, such as beauty, consumption, hypocrisy, and specific patterns. Cognitive semantics theory is employed to explain these meaning shifts through mechanisms of metaphor and metonymy. Furthermore, translation strategies are adapted to context, taking into account cultural differences between Mandarin and Indonesian. The findings offer insights into cross-cultural translation practices and deepen the understanding of word meaning evolution within a cognitive framework.